THE INFLUENCE OF PRICE, SERVICE QUALITY AND PRODUCT QUALITY ON CUSTOMER SATISFACTION AT BOUQUET.FILI STORE CIKARANG. - Firli Nurul Fajri; Prasetyo Harisandi; Yahya, Adibah (Jurnal Industri Kreatif dan Kewirausahaan, 2025)
This study aims to analyze the influence of price, service quality, and product quality on customer satisfaction at Store Bouquet.fili in Cikarang. The research is motivated by the increasing trend of gifting bouquets for various celebrations and the high level of competition in the bouquet industry, which requires business owners to deliver both innovation and excellent service. This is a descriptive quantitative research that collected data through questionnaires from 75 respondents who had previously made transactions at Store Bouquet.fili. The data was analyzed using SmartPLS4 through validity and reliability testing, followed by path analysis to determine variable relationships. The results show that price has a positive but not significant effect on customer satisfaction. On the other hand, service quality and product quality both have a positive and significant influence on customer satisfaction. Therefore, it is recommended that Store Bouquet.fili continues to enhance service and product quality as a key strategy to maintain customer loyalty and satisfaction. Future research is advised to include other variables such as promotion or brand image to obtain a more comprehensive understanding.